1998
DOI: 10.1152/ajpendo.1998.274.2.e246
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ovarian steroid hormones and thyroxine on calcitonin secretion in pregnant rats

Abstract: In the present study, the roles of ovarian steroid hormones and thyroxine (T4) in regulating the secretion of calcitonin (CT) in pregnant rats were examined. The levels of plasma progesterone, pre- and post-CaCl2plasma CT, and recovery time of plasma CT and calcium after calcium challenge were greatest in midterm pregnant rats. The levels of basal plasma progesterone, CT, calcium, and recovery time of plasma CT after calcium challenge were less in late pregnant rats, but basal plasma estradiol was highest in l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 18 publications
2
13
0
Order By: Relevance
“…Our results showed that, in intact rats, the anorectic effects of oestradiol were evident for 3 days, but from this time onwards they become less potent until they disappeared, which suggest a desensitization process. The 3-day period of time before the initiation of the suggested desensitization would allow oestradiol to exert its anorectic effect to the full during the physiological increases in the hormone -that is, during the 10-12 h of pro-oestrus in every oestrus cycle (Ter Haar 1972, Butcher et al 1974, Wade 1976) and during the last day of pregnancy (Lu et al 1998). It seems reasonable to argue that those anorectic episodes could be beneficial either for mating or for labour respectively, as they release the female from the constrains of searching for food during those periods of time.…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that, in intact rats, the anorectic effects of oestradiol were evident for 3 days, but from this time onwards they become less potent until they disappeared, which suggest a desensitization process. The 3-day period of time before the initiation of the suggested desensitization would allow oestradiol to exert its anorectic effect to the full during the physiological increases in the hormone -that is, during the 10-12 h of pro-oestrus in every oestrus cycle (Ter Haar 1972, Butcher et al 1974, Wade 1976) and during the last day of pregnancy (Lu et al 1998). It seems reasonable to argue that those anorectic episodes could be beneficial either for mating or for labour respectively, as they release the female from the constrains of searching for food during those periods of time.…”
Section: Discussionmentioning
confidence: 99%
“…The concentration of plasma E 2 was determined by RIA as previously described, using antiestradiol serum W-1 [Lu et al, 1998]. The sensitivity of E 2 RIA was 1 pg per assay tube.…”
Section: Ria Of Ementioning
confidence: 99%
“…Both estradiol and progesterone have been shown to cause an increase of in vitro CT release from the thyroid C cells of 8-day-old rats (Greenberg et al, 1986). Treatment of ovariectomized rats with progesterone results in an increase of basal and calcium-induced secretion of plasma CT (Lu et al, 1998). Therefore, the secretion of CT from the thyroid gland might be regulated by progesterone in humans; however, the mechanism of progesterone's effects on CT secretion is not clear.…”
Section: Introductionmentioning
confidence: 99%